2019
DOI: 10.1002/admi.201900640
|View full text |Cite
|
Sign up to set email alerts
|

Nature Helps: Toward Bioinspired Bactericidal Nanopatterns

Abstract: Development of synthetic bactericidal surfaces is a drug‐free route to the prevention of implant‐associated infections. Surface nanotopographies with specific dimensions have been shown to kill various types of bacterial strains through a mechanical mechanism, while regulating stem cell differentiation and tissue regeneration. The effective ranges of dimensions required to simultaneously achieve both aims are in the <200 nm range. Here, a nanoscale additive manufacturing (=3D printing) technique called elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 66 publications
2
51
0
2
Order By: Relevance
“…The results of this study showed that the cell wall of S. aureus could be mechanically penetrated by nanopatterns ( Figure 5) and be severely damaged with an unrecognizable morphology (Figure 3), as reported previously [25,30,37]. However, changing the interspacing of nanopatterns could drastically affect the percentage of the damaged cells.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The results of this study showed that the cell wall of S. aureus could be mechanically penetrated by nanopatterns ( Figure 5) and be severely damaged with an unrecognizable morphology (Figure 3), as reported previously [25,30,37]. However, changing the interspacing of nanopatterns could drastically affect the percentage of the damaged cells.…”
Section: Discussionsupporting
confidence: 81%
“…EBID was used to fabricate the desired nanopatterns on silicon substrates as described before [25]. Briefly, 1 × 1 cm 2 samples were prepared by cutting double-sided polished 4-inch (diameter = 10.16 cm) silicon wafers (thickness = 525 ± 25 µm, p-type), cleaning with nitric acid, and rinsing with deionized water subsequently.…”
Section: Nanopatterns Design Fabrication and Characterizationmentioning
confidence: 99%
See 3 more Smart Citations